Evaluating The Effect Of Volten Vr4® Kaempferia Parviflora Extracts On Blood Glucose Levels In Human Type-2 Diabetes Mellitus And Healthy Individual: A Case-control Study - Mohamad AS Mail,; Nordin MN ,; Ani IC ,; Jemberang J ,; Ishak R ,; Hasan AN ,; Ahmad MI ,; Omar MR ,; Hamzah R (MEDICAL ASSOCIATION OF THAILAND, 2024)
Indexed by Scopus